Athens or Rome? A New Perspective on the Political Philosophy of H. Arendt - Simas Čelutka (Problemos)
Hannah Arendt is widely known as a philosopher who attempted to rehabilitate the ancient Greek conception of politics. According to established readings of The Human Condition, Arendt is generally regarded as a ‘Graecophile’ whose thought is underwritten by ‘Athenian nostalgia’. Arendt’s sympathies for the Greeks are hard to deny: she did indeed turn to the Athenian understanding of politics in an attempt to crystallise in it the core elements of authentic politics. However, this interpretation is excessively one-sided. In Arendt’s view, the greatest contribution to the understanding of politics was offered by the Romans, not the Greeks. The Romans were much better at dealing with the problem of stability, continuity and order of politics. In Arendt’s view, an exclusive focus on action, spontaneity and extraordinary deeds threatens to destabilise the life of the political community. By introducing concepts such as tradition, authority, the sacredness of foundation, the law (lex), as well as the political significance of promise and forgiveness, the Romans opened up a dimension of political sedimentation which was alien to the Greeks. Political sedimentation provides safeguards, without which a sustainable political existence would become impossible.